(untitled) - Reade, Winwood (New York, 1931)
The Martyrdom of Man was a history of the world from an entirely new viewpoint, and was a prominent freethinking text of the late Nineteenth century. It is not an exaggeration to say that it provided a view of History as revolutionary as Darwin's view of Science - an entirely new and non-religious way of looking at the subject. It was very popular and influential on publication in the 1870's and long after - Arthur Conan Doyle, H.G. Wells and George Orwell were all heavily influenced William Winwood Reade (1838 - 1875) was a British historian, explorer, and philosopher. His major work, The Martyrdom of Man (1872), is a secular history of the Western world
Keywords: Văn minh,Civilization; Lịch sử; History